PENERAPAN MODEL PEMBELAJARAN VISUALIZATION, AUDITORY, KINESTHETIC (VAK) DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN HASIL BELAJAR IPA PADA SISWA KELAS IV SD NEGERI 1 DEPOKREJO TAHUN AJARAN 2015/2016 - Syarifuddin, Anis (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Visualization, Auditory, Kinesthetic Learning Using Concrete Media in Improving Natural Science Learning for the Fourth Grade Students of Elementary Schools. The objective of this collaborative Classroom Action Research (CAR) is to improve natural science learning for the fourth grade students of elementary schools.This research is conducted within two cycles in two meetings. Each cycle consisted of planning, action, observation, and reflection. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources and technique. The results of this research showed that the application of VAK learning using concrete media can improve natural science learning for the fourth grade students of elementary schools. Moreover, in the beginning of the treatments, the percentage of learning mastery of students is 53.57%, then it reached 89.12% in the end of treatments in the cycle two.Keywords:  VAK, concrete media, natural science, learning outcomes